Effect of cooking procedures of kiymali pide, a traditional Turkish fast-food, on destruction of Escherichia coli O157:H7 - İlhak, O. İrfan; Dikici, Abdullah; Can, Özlem Pelin; Şeker, Pınar; Öksüztepe, Gülsüm; Çalıcıoğlu, Mehmet (My University, 2013)
The objective of the present study was to obtain data about cooking time and temperature of kiymali pide in the restaurants and to investigate thermal inactivation of E. coli O157:H7 during experimental kiymali pide making. A field study was conducted in randomly selected 23 of 87 pide restaurants. Processing parameters including oven temperature, cooking period and post-cooking temperature were determined. Kiymali pide samples were prepared using ground beef filling experimentally inoculated with E. coli O157:H7 (7.6 log10 CFU/g). Pide samples were cooked at a conventional oven at 180 °C for 180, 240, 270, 300 and 330 s. Results of the current study suggest that cooking kiymali pide at 180 °C for at least 330 s (5.5 min) may provide sufficient food safety assurance (?6 log10 CFU/g) for E. coli O157:H7.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Escherichia coli O157:H7; Cooking time; Thermal destruction; Kiymali pide